Mundo do trabalho e pluralidade epistemológica: uma contribuição para o estudo da precariedade - Costa, Elizardo Scarpati; Almada, Pablo (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2018)
The article analyzes the centrality of the work to understand its current relevance. The sociology of work, by emphasizing historical-social transformations, presents different conceptions of work that fall within the analytical limits of the new dispositions of productive processes. A dialogue with such heuristic premises of work demonstrates that epistemological plurality must be considered to encompass the complexity of this world. It concludes that an approach related to the phenomenon of labor precariousness must oppose the abyssal theoretical and practical lines, for a plural incorporation of these various knowledge’s, effecting a reconstruction of social theory.